2016
DOI: 10.1073/pnas.1606383113
|View full text |Cite
|
Sign up to set email alerts
|

Superpriming of synaptic vesicles as a common basis for intersynapse variability and modulation of synaptic strength

Abstract: Glutamatergic synapses show large variations in strength and shortterm plasticity (STP). We show here that synapses displaying an increased strength either after posttetanic potentiation (PTP) or through activation of the phospholipase-C-diacylglycerol pathway share characteristic properties with intrinsically strong synapses, such as (i) pronounced short-term depression (STD) during high-frequency stimulation; (ii) a conversion of that STD into a sequence of facilitation followed by STD after a few conditioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
156
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(170 citation statements)
references
References 68 publications
5
156
0
Order By: Relevance
“…Differential calcium buffering has been suggested for lateral vs. medial calyx of Held synapses, which resulted in larger excitatory postsynaptic currents (EPSCs) in lateral MNTB neurons and might also contribute to more stable transmission in ongoing responses described in this present study (45). Additionally, an elevated state of release probability of synaptic vesicles, recently shown for the onset events in MNTB (46), may also be available in the ongoing response in neurons tuned to lower frequencies of the gerbil. However, because most research on the calyx of Held had been performed in mice or rats but not in ITD-using animals like gerbils (47) or guinea pigs (48), one can only speculate how constant synaptic delays are achieved in the subpopulation described above.…”
Section: Discussionmentioning
confidence: 53%
“…Differential calcium buffering has been suggested for lateral vs. medial calyx of Held synapses, which resulted in larger excitatory postsynaptic currents (EPSCs) in lateral MNTB neurons and might also contribute to more stable transmission in ongoing responses described in this present study (45). Additionally, an elevated state of release probability of synaptic vesicles, recently shown for the onset events in MNTB (46), may also be available in the ongoing response in neurons tuned to lower frequencies of the gerbil. However, because most research on the calyx of Held had been performed in mice or rats but not in ITD-using animals like gerbils (47) or guinea pigs (48), one can only speculate how constant synaptic delays are achieved in the subpopulation described above.…”
Section: Discussionmentioning
confidence: 53%
“…Each SV in the RRP has an intrinsic fusogenicity, and this property is apparently heterogeneous within the synapse (Ariel et al, 2013; Herman and Rosenmund, 2015; Lee et al, 2013; Nakamura et al, 2015; Rosenmund et al, 1993; Schlüter et al, 2006; Taschenberger et al, 2016). In particular, a subset of primed vesicles has been proposed to be in a “superprimed” state with a significantly higher release probability than the remainder of the SVs (Lee et al, 2013; Schlüter et al, 2006; Taschenberger et al, 2016). A recent study revealed that the superprimed pool of SVs is enhanced by phorbol esters, and this pool was transiently expanded following high-frequency stimulation, thereby contributing to post-tetanic potentiation (PTP) (Taschenberger et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a subset of primed vesicles has been proposed to be in a “superprimed” state with a significantly higher release probability than the remainder of the SVs (Lee et al, 2013; Schlüter et al, 2006; Taschenberger et al, 2016). A recent study revealed that the superprimed pool of SVs is enhanced by phorbol esters, and this pool was transiently expanded following high-frequency stimulation, thereby contributing to post-tetanic potentiation (PTP) (Taschenberger et al, 2016). Our data along with previous studies support an important post-priming function of Munc13 (Basu et al, 2007; Lou et al, 2008; Madison et al, 2005; Rhee et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…S2). Monte Carlo simulations of these results indicated that, at 4 wk, the release probability of docked SVs is reduced for the first and second stimulation, possibly reflecting a decrease of the percentage of high release probability "superprimed" SVs (39,40). In addition, simulations indicated a reduction of the initial occupancy of the replacement site at 4 wk (Fig.…”
mentioning
confidence: 87%